C-reactive protein orchestrates acute allograft rejection in vascularized composite allotransplantation via selective activation of monocyte subsets - Kiefer, Jurij; Zeller, Johannes; Schneider, Laura; Thomé, Julia; McFadyen, James D.; Hörbrand, Isabel; Lang, Friederike; Deiss, Emil; Bogner, Balázs; Schaefer, AnnaLena; Chevalier, Nina; Horner, Verena K.; et al. (Journal of advanced research, 2025)
Introduction - Despite advancements in transplant immunology and vascularized composite allotransplantation (VCA), the longevity of allografts remains hindered by the challenge of allograft rejection. The acute-phase response, an immune-inflammatory reaction to ischemia/reperfusion that occurs directly after allogeneic transplantation, serves as a catalyst for graft rejection. This immune response is orchestrated by acute-phase reactants through intricate crosstalk with the mononuclear phagocyte system. - Objective - C-reactive protein (CRP), a well-known marker of inflammation, possesses pro-inflammatory properties and exacerbates ischemia/reperfusion injury. Thus, we investigated how CRP impacts acute allograft rejection. - Methods - Prompted by clinical observations in facial VCAs, we employed a complex hindlimb transplantation model in rats to investigate the direct impact of CRP on transplant rejection. - Results - Our findings demonstrate that CRP expedites allograft rejection and diminishes allograft survival by selectively activating non-classical monocytes. Therapeutic stabilization of CRP abrogates this activating effect on monocytes, thereby attenuating acute allograft rejection. Intravital imagining of graft-infiltrating, recipient-derived monocytes during the early phase of acute rejection corroborated their differential regulation by CRP and their pivotal role in driving the initial stages of graft rejection. - Conclusion - The differential activation of recipient-derived monocytes by CRP exacerbates the innate immune response and accelerates clinical allograft rejection. Thus, therapeutic targeting of CRP represents a novel and promising strategy for preventing acute allograft rejection and potentially mitigating chronic allograft rejection.